Taxonomic analysis and economic significance of the Shchaul tract flora within the Marmaros massif (Ukrainian Carpathians) - Moskaliuk, B.; Felbaba-Klushyna, L.; Melesh, Ye. (Scientific Progress & Innovations, 2024)
In the modern conditions of increased anthropogenic impact on natural ecosystems, the study of regional flora, which initiates the monitoring of phytodiversity, is of great importance. Even now, little studied remains the flora of the territories of state forestry research enterprises, which can serve not only as economic sites, but also as scientific training grounds for observing changes occurring as a result of management and climate changes. The purpose of our work was to find out the taxonomic diversity of the flora of vascular plants of the Shchaul tract of the Marmarosh massif of the Ukrainian Carpathians (Bohdan village, Rakhiv district, Transcarpathian region) and to assess its economic importance. Based on the results of the research, it was established that the flora of the Schaul tract includes 220 species, 167 genera, and 60 families of vascular plants. The vast majority of species are represented by the division Magnoliophyta, which accounts for 95.0 % of the total number of species, while the division Lycopodiophyta has only one species (0.4 %). Divisions Equisetophyta and Pinophyta - three species each (1.4 %). The division Polypodiophyta counts four species, which is 1.8%. Among the first eleven families, which are the richest in species, the leading place belongs to the families: Asteraceae – 27 species (12.2 %), Ranunculaceae – 16 species (7.2 %), Poaceae and Lamiaceae – 15 species each (6.8 %), Rosaceae – 13 species (5.8 %), Brassicaceae – 9 species (4.0 %), Caryophyllaceae and Fabaceae 8 species each (3.6 %), Apiaceae, Polygonaceae and Scrophulariaceae 6 species each (2.7 %). Their share accounts for 58.1 % of the species diversity of the studied flora. The rest of the families are less numerous in terms of species, they account for 41.9 %. It was established that in general the taxonomic structure of the flora of the Shchaul tract is similar to the regional flora, but it has certain signs of synanthropization, manifested, in particular, in the position of the families Lamiaceae and Polygonaceae. Data on the economic assessment of the flora are provided, 19 economically important groups of species are highlighted, which is a high indicator of the considerable practical value of the studied flora. 177 species of decorative plants, 134 medicinal plant species, 102 fodder species, 82 honey species, 47 edible species, 36 poisonous species, as well as 59 species of weeds, etc., were identified. Other groups are represented by a small number of species. The growth of 7 plant species included in the Red Book of Ukraine was noted: Galanthus nivalis L., Crocus heuffelianus Herb., Scopolia carniolica Jacq., Epipactis helleborine (L.) Crantz, Pinus cembra L., Orchis fuchsii Druce, Listera ovata (L.) R.Br. The presence of such species is an indicator of the nature conservation and scientific value of the studied area. The obtained data can be used to improve the forestry management methods of the Shchaul Forestry.